Nilai Moral dan Pendidikan Pembangunan Karakter dalam Cerita Rakyat Batu Gantung - Julia Rheinta Nata; Yenita Br. Sembiring (Jurnal Ilmiah Wahana Pendidikan, 2020)
This research investigated Moral Value and Character Building Education in Folklore of Batu Gantung. In daily individually with society, we must have culture, attitude, character. It depends in moral and ethnic that can build our national character. The research aimed to find out the moral values and character building education that implied in Folklore of Batu Gantung. The research was conducted in the Public Library and National Library. This research was conducted by using Library Research Method. The instruments for collecting data was library research and documentation. The data analysis was the result of research in Public Library and National Library or some library which keep many documents of Folklore of Batu Gantung. After analyzing the folklore, the researcher found some moral lessons and character building education such as; strong belief, kind-hearted, love affection, sacrificing for others, bravery, enthusiasm, fairness, responsibility, citizenship and caring.